MOTIVATION AND COMMUNICATIVE ATTITUDES AMONG JAPANESE EFL PUPILS - Adachi, Rie (Universitas Pendidikan Indonesia, 2015)
This paper describes how gender and age affect Japanese pupilsâ€™ motivation for learning English and their attitudes to communication with people from different cultures. A new foreign language curriculum was introduced to Japanese elementary schools in 2011. Although each school can officially choose any foreign language in its own right, most elementary schools are now conducting English activity. However, as most homeroom teachers lack both experiences and qualifications for teaching English, this activity puts them under pressure. In addition, the number of foreign assistant language teachers (ALTs) is not sufficient in most elementary schools. The writer surveyed fifth and sixth grade pupilsâ€™ motivation and their communicative attitudes in Japan during 2010, before the new course program, â€œforeign language activities,â€ began in 2011. The data were collected from three elementary schools in Japan via a questionnaire. The items on the questionnaire are related to motivational attitudes, orientations (reasons for studying a foreign language), communicative attitudes and some other variables relevant to learning foreign languages. The main focus of this study is to examine motivational and attitudinal variables among the pupils with regard to learning English, especially gender and age effects on these variables. The results show that girls generally have higher scores on motivation and communicative attitudes. Most previous studies have also shown that girls generally have a positive attitude toward learning a foreign language. This study argues that the reason behind this positive attitude toward learning English is due to their positive attitude toward communication in general. With regard to the age, there are a few differences between two school grades. As there is only one year difference in age between fifth and sixth grade pupils, the result is to be expected. The study suggests that Japanese elementary schools face a number of difficulties teaching English as it is difficult for teachers to motivate all pupils.